Positive electrode and lithium secondary battery including same

JP7635400B2Active Publication Date: 2025-02-25LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023545353
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-26
Filing Date
2022-02-25
Publication Date
2025-02-25
Estimated Expiration
2042-02-25

AI Technical Summary

Benefits of technology

【0009】 本発明の正極は、2層の正極活物質層を含み、電解液と接触する上部正極活物質層にコバルトに対するニッケルのモル比が相対的に小さい正極活物質を配置して正極活物質層の内部でのリチウム移動性を向上させることにより、寿命特性が改善されるようにした。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635400000001
    Figure 0007635400000001
Patent Text Reader

Abstract

The present invention relates to a positive electrode for a lithium secondary battery. The positive electrode of the present invention includes a positive electrode current collector, a first positive electrode active material layer formed on the positive electrode current collector and including a first positive electrode active material, and a second positive electrode active material layer formed on the first positive electrode active material layer and including a second positive electrode active material, the first positive electrode active material and the second positive electrode active material including a lithium nickel-cobalt oxide having a nickel content of 80 mol% or more relative to all metal components excluding lithium, the first positive electrode active material having a molar ratio of nickel to cobalt of 18 or more, and the second positive electrode active material having a molar ratio of nickel to cobalt of less than 18.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0026597, filed on February 26, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated as part of this specification.

[0002] The present invention relates to a positive electrode and a lithium secondary battery including the same, and more particularly to a high-loading positive electrode having improved life characteristics and a lithium secondary battery including the same. [Background technology]

[0003] 2. Description of the Related Art As demand for mobile devices, electric vehicles, and the like increases, the demand for secondary batteries as energy sources is rapidly increasing. Among secondary batteries, lithium secondary batteries, which have high energy density and a low self-discharge rate, have become commercially available and are widely used.

[0004] In recent years, the demand for high-capacity batteries has been increasing in industrial fields such as electric vehicles and energy storage systems (ESS). As a result, the development of high-loading positive electrodes that contain a high loading amount of high-nickel (High-Ni) positive electrode active material with excellent capacity characteristics is progressing.

[0005] Although a high-loading positive electrode has the advantage of excellent capacity characteristics, as the loading amount increases, the movement of Li inside the positive electrode active material layer becomes difficult, so that a relatively large amount of lithium ions moves to the surface of the positive electrode active material layer rather than inside, which causes rapid electrode deterioration and reduces life characteristics. Therefore, there is a need to develop a high-loading electrode with excellent life characteristics. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention is intended to solve the above problems, and provides a high-loading positive electrode having improved life characteristics by controlling the molar ratio of nickel to cobalt in a positive electrode active material located inside and on the surface of a positive electrode active material layer to improve lithium mobility inside the positive electrode active material layer, and a lithium secondary battery including such a positive electrode. [Means for solving the problem]

[0007] According to one embodiment, the present invention provides a positive electrode including a positive electrode current collector, a first positive electrode active material layer formed on the positive electrode current collector and including a first positive electrode active material, and a second positive electrode active material layer formed on the first positive electrode active material layer and including a second positive electrode active material, wherein the first positive electrode active material and the second positive electrode active material include a lithium nickel-cobalt-based oxide having a nickel content of 80 mol% or more relative to all metal components excluding lithium, and the first positive electrode active material has a molar ratio of nickel to cobalt of 18 or more, and the second positive electrode active material has a molar ratio of nickel to cobalt of less than 18.

[0008] According to another embodiment, the present invention provides a lithium secondary battery including a positive electrode as described above. Effect of the Invention

[0009] The positive electrode of the present invention includes two positive electrode active material layers, and a positive electrode active material having a relatively small molar ratio of nickel to cobalt is disposed in the upper positive electrode active material layer that contacts the electrolyte, thereby improving lithium mobility within the positive electrode active material layer and improving life characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be specifically described below.

[0011] As a result of extensive research into improving the life characteristics of lithium secondary batteries using high-loading positive electrodes, the inventors discovered that the life characteristics of high-loading electrodes can be improved by forming a positive electrode active material layer into a two-layer structure that satisfies a specific nickel / cobalt molar ratio, thereby completing the present invention.

[0012] positive electrode The positive electrode according to the present invention includes a positive electrode current collector, a first positive electrode active material layer formed on the positive electrode current collector and including a first positive electrode active material, and a second positive electrode active material layer formed on the first positive electrode active material layer and including a second positive electrode active material.

[0013] The positive electrode current collector is for supporting the positive electrode active material layer, and may be a positive electrode current collector generally used in the art. For example, the positive electrode current collector may be a film, sheet, foil, net, porous body, foam, or nonwoven fabric made of a material such as aluminum, stainless steel, nickel, or titanium.

[0014] The positive electrode current collector may be surface-treated to improve physical properties such as adhesive strength, strength, etc. For example, the positive electrode current collector may include a coating film made of a material such as carbon, nickel, titanium, silver, etc., on the surface, and may have fine irregularities formed thereon.

[0015] The positive electrode current collector may usually have a thickness of 3 μm to 500 μm.

[0016] The first positive electrode active material layer is a positive electrode active material layer formed on the positive electrode current collector, that is, a lower positive electrode active material layer, and includes a first positive electrode active material.

[0017] The first positive electrode active material is a lithium transition metal oxide containing nickel and cobalt, specifically, a lithium nickel-cobalt oxide in which the nickel content relative to the metal components other than lithium is 80 mol% or more, preferably 90 mol% or more, more preferably 90 mol% to 95 mol%, and the molar ratio of nickel to cobalt is 18 or more, preferably 18 to 50. When the nickel content of the first positive electrode active material satisfies the above range, high capacity characteristics can be realized. On the other hand, when the molar ratio of nickel to cobalt of the first positive electrode active material deviates from the above range, the effect of improving lithium mobility inside the positive electrode active material layer is weak.

[0018] Preferably, the first positive electrode active material may be a lithium transition metal oxide represented by the following [Chemical Formula 1].

[0019] [Chemical formula 1] Li a1 [Ni x1 Co y1 M 1 Z1 M 2 w1 ]O2

[0020] In the above formula 1, M 1 may be Mn, Al, or a combination thereof, preferably Mn or a combination of Mn and Al.

[0021] M 2 may be one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P and S.

[0022] The a1 indicates the molar ratio of lithium in the lithium transition metal oxide, and may be 0.8≦a1≦1.2, 0.9≦a1≦1.1, or 0.95≦a1≦1.1.

[0023] The x1 represents the molar ratio of nickel to the metal components excluding lithium in the lithium transition metal oxide, and it may be 0.90 ≦ x1 < 1, 0.90 ≦ x1 ≦ 0.98, or 0.90 ≦ x1 ≦ 0.95. When the molar ratio of nickel satisfies the above range, excellent capacity characteristics can be realized.

[0024] The y1 represents the molar ratio of cobalt to the metal components excluding lithium in the lithium transition metal oxide, and it may be 0 < y1 < 0.10, 0.01 ≦ y1 < 0.10, or 0.01 ≦ y1 ≦ 0.06.

[0025] The z1 represents the molar ratio of M to the metal components excluding lithium in the lithium transition metal oxide 1 and it may be 0 < z1 < 0.10, 0.01 ≦ z1 ≦ 0.08, or 0.01 ≦ z1 ≦ 0.06.

[0026] The w1 represents the molar ratio of M to the metal components excluding lithium in the lithium transition metal oxide 2 and it may be 0 ≦ w1 < 0.10, 0 ≦ w1 ≦ 0.05, or 0 ≦ w1 ≦ 0.02.

[0027] On the other hand, in the above Chemical Formula 1, the molar ratio of nickel to cobalt, that is, x1 / y1, may be 18 or more, preferably 18 to 50. When x1 / y1 is less than 18, the effect of improving lithium mobility in the high-loading positive electrode active material layer is weak.

[0028] On the other hand, the first positive electrode active material may have a cation mixing rate of, for example, more than 1.2%, preferably more than 1.2% and 2.0% or less.

[0029] The first positive electrode active material may be included in an amount of 80% by weight or more, preferably 80% by weight to 100% by weight, and more preferably 85% by weight to 98% by weight, based on the total weight of the first positive electrode active material layer. When the content of the first positive electrode active material satisfies the above range, lithium ions can move more smoothly during charging and discharging in a high loading electrode.

[0030] The first positive electrode active material layer may have a thickness of 30 μm to 300 μm, preferably 50 μm to 200 μm, and more preferably 70 μm to 150 μm. When the thickness of the first positive electrode active material layer satisfies the above range, high loading characteristics can be achieved.

[0031] Next, the second positive electrode active material layer is a positive electrode active material layer formed on the first positive electrode active material layer, that is, an upper positive electrode active material layer, and includes a second positive electrode active material.

[0032] The second positive electrode active material is a lithium transition metal oxide containing nickel and cobalt, specifically, a lithium nickel-cobalt oxide in which the nickel content relative to the metal components excluding lithium is 80 mol % or more, preferably 80 mol % or more and less than 90 mol %, and more preferably 81 mol % to 89 mol %, and the molar ratio of nickel to cobalt is less than 18, preferably 5 to 17.8, and more preferably 7 to 17.6.

[0033] When the nickel content of the second positive electrode active material satisfies the above range, high capacity characteristics can be realized. Also, when the molar ratio of nickel to cobalt of the second positive electrode active material satisfies the above range, the movement of lithium ions is balanced between the surface and the interior of the positive electrode active material layer, and rapid deterioration of the structure on the surface of the positive electrode active material layer can be prevented.

[0034] Preferably, the second positive electrode active material may be a lithium transition metal oxide represented by the following [Chemical Formula 2].

[0035] [Chemical formula 2] Li a2 [Nix2 Co y2 M 3 Z2 M 4 w2 O2

[0036] In the above Chemical Formula 2, M 3 may be Mn, Al, or a combination thereof, preferably Mn or a combination of Mn and Al.

[0037] M 4 may be one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S.

[0038] The a2 represents the molar ratio of lithium in the lithium transition metal oxide, and may be 0.8 ≦ a2 ≦ 1.2, 0.9 ≦ a2 ≦ 1.1, or 0.95 ≦ a2 ≦ 1.1.

[0039] The x2 represents the molar ratio of nickel to the metal component excluding lithium in the lithium transition metal oxide, and may be 0.80 ≦ x2 < 0.90, 0.81 ≦ x2 ≦ 0.89, or 0.83 ≦ x2 ≦ 0.89. When the molar ratio of nickel satisfies the above range, excellent capacity characteristics can be realized.

[0040] The y2 represents the molar ratio of cobalt to the metal component excluding lithium in the lithium transition metal oxide, and may be 0 < y2 < 0.20, 0.01 ≦ y2 < 0.20, or 0.01 ≦ y2 ≦ 0.15.

[0041] The z2 represents the molar ratio of M 3 to the metal component excluding lithium in the lithium transition metal oxide, and may be 0 < z2 < 0.20, 0.01 ≦ z2 < 0.20, or 0.01 ≦ z2 ≦ 0.15.

[0042] The w2 represents the molar ratio of M 4and may be 0≦w2<0.20, 0≦w2≦0.10, or 0≦w2≦0.05.

[0043] On the other hand, in the above Chemical Formula 2, the molar ratio of nickel to cobalt, i.e., x2 / y2, may be less than 18, preferably 5 to 17.8, and more preferably 7 to 17.6. When x2 / y2 is 18 or more, the effect of improving lithium mobility in the high-loading positive electrode active material layer is weak.

[0044] Meanwhile, the second positive electrode active material has a cation mixing ratio of 1.2% or less, preferably 1.0% or less. When the cation mixing ratio of the second positive electrode active material satisfies the above range, that is, when the cation mixing ratio of the second positive electrode active material is lower than that of the first positive electrode active material, the effect of further improving lithium mobility can be obtained.

[0045] The second positive electrode active material may be included in an amount of 80% by weight or more, preferably 80% by weight to 100% by weight, and more preferably 85% by weight to 98% by weight, based on the total weight of the second positive electrode active material layer. When the content of the second positive electrode active material satisfies the above range, lithium ions can move smoothly during charging and discharging in a high loading electrode.

[0046] The second positive electrode active material layer may have a thickness of 10 μm or less, preferably 1 to 10 μm, and more preferably 2 to 5 μm. When the thickness of the second positive electrode active material layer satisfies the above range, the decrease in energy density can be minimized and the deterioration of life due to the imbalance in lithium mobility can be effectively suppressed.

[0047] Meanwhile, the first and second positive electrode active material layers may further include a conductive material and a binder in addition to the positive electrode active material.

[0048] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not undergo chemical change in the battery that is constructed and has electronic conductivity.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these can be used alone or in combination.

[0049] The conductive material may be contained in an amount of 10% by weight or less, preferably 0.2 to 5% by weight, and more preferably 0.5 to 2% by weight, based on the total weight of the first positive electrode active material layer or the second positive electrode active material layer. When the content of the conductive material satisfies the above range, the electrochemical performance and energy density can be optimized.

[0050] The binder is used to improve adhesion between positive active material particles and between the positive active material and the current collector, and may be any binder commonly known in the art.

[0051] For example, the binder may be polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof. Among these, one type may be used alone, or two or more types may be used in combination.

[0052] The binder may be contained in an amount of 10% by weight or less, preferably 0.2 to 5% by weight, and more preferably 0.5 to 2% by weight, based on the total weight of the first positive electrode active material layer or the second positive electrode active material layer. When the binder content satisfies the above range, the electrochemical performance and energy density can be optimized.

[0053] On the other hand, the positive electrode has a loading of 4 mAh / cm 2 More than 4mAh / cm 2 ~20mAh / cm 2 When the loading amount satisfies the above range, a high energy density can be achieved.

[0054] The positive electrode according to the present invention may be manufactured by preparing a first positive electrode slurry composition including a first positive electrode active material and a second positive electrode slurry composition including a second positive electrode active material, and then sequentially applying the first positive electrode slurry composition and the second positive electrode slurry composition.

[0055] For example, the positive electrode according to the present invention may be manufactured by coating a first positive electrode slurry composition on a positive electrode current collector and drying to form a first positive electrode active material layer, coating a second positive electrode slurry composition on the first positive electrode active material layer and drying to form a second positive electrode active material layer, and then rolling.

[0056] Alternatively, the positive electrode according to the present invention can be manufactured by a method in which a first positive electrode slurry composition is applied onto a separate support and dried to form a first positive electrode active material layer, a second positive electrode slurry composition is applied onto the first positive electrode active material layer and dried to form a second positive electrode active material layer, and then a laminate of the first positive electrode active material layer and the second positive electrode active material layer is separated from the support, and the laminate is laminated onto a positive electrode current collector.

[0057] Meanwhile, the first and second positive electrode slurry compositions may be prepared by dispersing a positive electrode active material, a conductive material, and a binder in a solvent, and the solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, or a mixture thereof. The solvent may be used in an amount that dissolves or disperses the positive electrode active material, conductive material, and binder and has a viscosity that allows excellent thickness uniformity when applied, taking into consideration the coating thickness of the positive electrode slurry and the manufacturing yield.

[0058] Lithium secondary battery Next, the lithium secondary battery according to the present invention will be described.

[0059] The lithium secondary battery according to the present invention includes the above-mentioned positive electrode according to the present invention. Specifically, the lithium secondary battery according to the present invention may include the positive electrode according to the present invention, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is as described above, a detailed description will be omitted, and only other components will be described in detail below.

[0060] The negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0061] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and can be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector can usually have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector can be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0062] The negative electrode active material layer may optionally include a binder and a conductive material in addition to the negative electrode active material.

[0063] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these can be used. In addition, a thin film of metallic lithium can also be used as the negative electrode active material. Furthermore, low-crystalline carbon, high-crystalline carbon, and the like can all be used as the carbonaceous material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0064] The negative electrode active material may be contained in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.

[0065] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be included in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0066] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be contained in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0067] The negative electrode active material layer can be produced by applying a negative electrode slurry composition, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material in a solvent, onto a negative electrode current collector and drying the composition, or by casting the negative electrode slurry composition onto another support, and then peeling the composition from the support to obtain a film, which can be laminated onto the negative electrode current collector.

[0068] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to the movement of electrolyte ions and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric substance may be used to ensure heat resistance or mechanical strength, and may be selectively used as a single layer or multilayer structure.

[0069] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0070] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0071] The organic solvent can be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of solvents that can be used include carbonate solvents such as PC (carbonate), alcohol solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, or sulfolanes.

[0072] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2.LiCl, LiI or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively. EXAMPLES

[0073] The present invention will be described in more detail with reference to the following specific examples. However, the embodiments according to the present invention can be modified in various different forms, and the scope of the present invention should not be construed as being limited to the following detailed examples. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0074] Example 1 The first positive electrode active material is LiNi with a cation mixing rate of 1.3%. 0.9 Co 0.05 Mn 0.05 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0075] The second positive electrode active material is LiNi, which has a cation mixing rate of less than 1%. 0.83 Co 0.11 Mn 0.06A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0076] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to prepare a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 6.85 mAh / cm. 2 It was.

[0077] Example 2 The first positive electrode active material is LiNi with a cation mixing rate of 1.5%. 0.9 Co 0.04 Mn 0.06 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0078] The second positive electrode active material is LiNi, which has a cation mixing rate of less than 1%. 0.85 Co 0.07 Mn 0.08 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0079] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to prepare a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 6.85 mAh / cm. 2 It was.

[0080] Example 3 The first positive electrode active material is LiNi with a cation mixing ratio of 1.7%. 0.9 Co 0.02 Mn 0.08 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0081] The second positive electrode active material is LiNi with a cation mixing rate of 1.2%. 0.88 Co 0.05 Mn 0.07 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0082] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to manufacture a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 6.9 mAh / cm. 2 It was.

[0083] Example 4 The first positive electrode active material is LiNi with a cation mixing rate of 1.3%. 0.92 Co 0.05 Mn 0.03 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0084] The second positive electrode active material is LiNi, which has a cation mixing rate of less than 1%. 0.83 Co 0.11 Mn 0.06 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0085] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to manufacture a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 6.9 mAh / cm. 2 It was.

[0086] Example 5 The first positive electrode active material is LiNi with a cation mixing rate of 1.4%. 0.92 Co 0.04 Mn 0.04 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0087] The second positive electrode active material is LiNi, which has a cation mixing rate of less than 1%. 0.85 Co 0.07 Mn 0.08 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0088] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to manufacture a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 6.9 mAh / cm. 2 It was.

[0089] Example 6 The first positive electrode active material is LiNi with a cation mixing ratio of 1.7%. 0.92 Co 0.02 Mn 0.06 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0090] The second positive electrode active material is LiNi with a cation mixing rate of 1.2%. 0.88 Co 0.05 Mn 0.07 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0091] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to manufacture a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 6.9 mAh / cm. 2 It was.

[0092] Example 7 The first positive electrode active material is LiNi with a cation mixing rate of 1.4%. 0.94 Co 0.05 Mn 0.01 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0093] The second positive electrode active material is LiNi, which has a cation mixing rate of less than 1%. 0.83 Co 0.11 Mn 0.06 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0094] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to manufacture a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 6.9 mAh / cm. 2 It was.

[0095] Example 8 The first positive electrode active material is LiNi with a cation mixing rate of 1.5%. 0.94 Co 0.04 Mn 0.02 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0096] The second positive electrode active material is LiNi, which has a cation mixing rate of less than 1%. 0.85 Co 0.07 Mn 0.06 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0097] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to manufacture a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 7 mAh / cm. 2 It was.

[0098] Example 9 The first positive electrode active material is LiNi with a cation mixing ratio of 1.7%. 0.94 Co 0.02 Mn 0.04 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0099] The second positive electrode active material is LiNi with a cation mixing rate of 1.2%. 0.88 Co 0.05 Mn 0.07 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0100] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to manufacture a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 7 mAh / cm. 2 It was.

[0101] Comparative Example 1 The positive electrode active material is LiNi with a cation mixing rate of 1.5%. 0.9 Co 0.04 Mn 0.06 A positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0102] The positive electrode slurry composition was applied to an aluminum current collector, and then dried at 130° C. and rolled to prepare a positive electrode. The thickness of the positive electrode active material layer was 100 μm, and the loading capacity of the positive electrode was 6.9 mAh / cm 2 It was.

[0103] Comparative Example 2 The positive electrode active material is LiNi with a cation mixing rate of 1.4%. 0.92 Co 0.04 Mn 0.04A positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0104] The positive electrode slurry composition was applied to an aluminum current collector, and then dried at 130° C. and rolled to prepare a positive electrode. The thickness of the positive electrode active material layer was 100 μm, and the loading amount of the positive electrode was 7 mAh / cm 2 It was.

[0105] Comparative Example 3 The positive electrode active material is LiNi with a cation mixing rate of 1.5%. 0.94 Co 0.04 Mn 0.02 A positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0106] The positive electrode slurry composition was applied to an aluminum current collector, and then dried at 130° C. and rolled to prepare a positive electrode. The thickness of the positive electrode active material layer was 100 μm, and the loading amount of the positive electrode was 7 mAh / cm 2 It was.

[0107] Comparative Example 4 The first positive electrode active material is LiNi with a cation mixing rate of 1.5%. 0.9 Co 0.04 Mn 0.06 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0108] The second positive electrode active material is LiNi with a cation mixing rate of 1.3%.0.9 Co 0.05 Mn 0.05 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0109] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to manufacture a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 6.9 mAh / cm. 2 It was.

[0110] Comparative Example 5 The first positive electrode active material is LiNi with a cation mixing rate of 1.2%. 0.88 Co 0.05 Mn 0.07 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0111] The second positive electrode active material is LiNi, which has a cation mixing rate of less than 1%. 0.85 Co 0.07 Mn 0.08 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0112] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to manufacture a positive electrode. At this time, based on the cross section of the positive electrode, the thickness of the first positive electrode active material layer was 98 μm, the thickness of the second positive electrode active material layer was 2 μm, and the loading amount of the positive electrode was 6.9 mAh / cm. 2 It was.

[0113] Comparative Example 6 The first positive electrode active material is LiNi having a cation mixing rate of less than 1%. 0.85 Co 0.07 Mn 0.08 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder were mixed in an N-methylpyrrolidone solvent so that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1 to prepare a first positive electrode slurry.

[0114] The second positive electrode active material is LiNi with a cation mixing rate of 1.5%. 0.9 Co 0.04 Mn 0.06 A second positive electrode slurry was prepared by mixing O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder in an N-methylpyrrolidone solvent such that the weight ratio of the positive electrode active material:conductive material:binder was 98.5:0.5:1.

[0115] A first positive electrode slurry composition was applied to an aluminum current collector and dried to form a first positive electrode active material layer, and then a second positive electrode slurry composition was applied on the first positive electrode active material layer and then dried at 130° C. and rolled to prepare a positive electrode. Based on the cross section of the positive electrode, the first positive electrode active material layer had a thickness of 98 μm, the second positive electrode active material layer had a thickness of 2 μm, and the loading amount of the positive electrode was 6.8 mAh / cm. 2 It was.

[0116] Experimental Example 1 An electrode assembly was prepared by interposing a porous polyethylene separator between the positive electrode prepared according to Examples 1 to 9 and Comparative Examples 1 to 6 and the lithium metal negative electrode. Then, an electrolyte prepared by adding 2 wt % of vinyl carbonate (VC) to an organic solvent in which ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) were mixed in a ratio of 3:4:3 and dissolving 1M LiPF6 was injected to prepare a lithium secondary battery.

[0117] Each of the lithium secondary batteries prepared as above was charged at a constant current of 0.1 C at 25° C. up to 4.25 V, and then discharged at a constant current of 0.1 C down to 2.5 V to measure the discharge capacity.

[0118] The measurement results are shown in Table 1 below.

[0119] Experimental Example 2 Each of the lithium secondary batteries manufactured in Experimental Example 1 above was charged at 45° C. with a constant current of 0.3 C up to 4.25 V and then discharged at a constant current of 0.3 C up to 2.5 V, which constitutes one cycle. 100 charge / discharge cycles were then performed, and the capacity retention rate after the 100 cycles was measured to determine the life characteristics.

[0120] The measurement results are shown in Table 1 below.

[0121] [Table 1]

[0122] As shown in Table 1 above, in the case of the lithium secondary batteries using the positive electrodes of Examples 1 to 9 in which the Ni / Co ratios of the first positive electrode active material and the second positive electrode active material fell within the range of the present invention, the life characteristics were significantly improved compared to the lithium secondary batteries using the positive electrodes of Comparative Examples 1 to 6.

Claims

1. a positive electrode current collector; a first positive electrode active material layer formed on the positive electrode current collector and including only a first positive electrode active material as a positive electrode active material; and a second positive electrode active material layer formed on the first positive electrode active material layer and including only a second positive electrode active material as a positive electrode active material, The first positive electrode active material and the second positive electrode active material each include a lithium nickel-cobalt-based oxide in which the nickel content of all metal components excluding lithium is 80 mol % or more; The first positive electrode active material has a molar ratio of nickel to cobalt of 18 or more; the second positive electrode active material has a molar ratio of nickel to cobalt of less than 18; The positive electrode has a loading amount of 4 mAh / cm 2 or more.

2. The first positive electrode active material has a molar ratio of nickel to cobalt of 18 to 50; 10. The positive electrode of claim 1, wherein the second positive electrode active material has a molar ratio of nickel to cobalt of 5 to 17.

8.

3. The first positive electrode active material has a cation mixing rate of more than 1.2%; The positive electrode of claim 1 or 2, wherein the second positive electrode active material has a cation mixing rate of 1.2% or less.

4. The first positive electrode active material has a cation mixing rate of 1.2% to 2%; The positive electrode according to claim 3 , wherein the second positive electrode active material has a cation mixing rate of 1.0% or less.

5. The first positive electrode active material has a nickel content of 90 mol% or more relative to all metal components excluding lithium, The positive electrode according to any one of claims 1 to 4, wherein the second positive electrode active material has a nickel content of 80 mol % or more and less than 90 mol % relative to all metal components excluding lithium.

6. The positive electrode according to any one of claims 1 to 5, wherein the first positive electrode active material includes a first lithium nickel-cobalt oxide represented by the following [Chemical Formula 1]: [Chemical formula 1] Li a1 [Ni x1 Co y1 M 1 Z1 M 2 w1 ]O 2 In the above Chemical Formula 1, M 1 is Mn, Al, or a combination thereof; M 2 is one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S; 0.8≦a1≦1.2, 0.90≦x1<1, 0<y1<0.10, 0<z1<0.10, 0≦w1<0.10, and 18≦x1 / y1.

7. The positive electrode according to any one of claims 1 to 6, wherein the second positive electrode active material includes a second lithium nickel-cobalt-based oxide represented by the following [Chemical Formula 2]: [Chemical formula 2] Li a2 [Ni x2 Co y2 M 3 Z2 M 4 w2 ]O 2 In the above Chemical Formula 2, M 3 is Mn, Al, or a combination thereof; M 4 is one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S; 0.8≦a2≦1.2, 0.80≦x2<0.90, 0<y2<0.20, 0<z2<0.20, 0≦w2<0.20, and x2 / y2<18.

8. The positive electrode according to any one of claims 1 to 7, wherein the second positive electrode active material layer has a thickness of 10 µm or less.

9. The positive electrode has a loading capacity of 4 mAh / cm 2 ~20mAh / cm 2 The positive electrode according to any one of claims 1 to 8.

10. A lithium secondary battery comprising the positive electrode according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Positive electrode for secondary battery and lithium secondary battery including the same

    JP2020512669A

  • Positive electrode active material for secondary battery, method for producing the same, and lithium secondary battery including the same

    JP2021507497A

  • Positive Electrode Material for Secondary Battery and Lithium Secondary Battery Including the Same

    US20200266438A1

  • Positive electrode active substance, positive electrode, and lithium ion secondary cell

    WO2018135253A1